2014
DOI: 10.1177/0960327114522500
|View full text |Cite
|
Sign up to set email alerts
|

Neonicotinoid insecticide exposures reported to six poison centers in Texas

Abstract: Neonicotinoids are a relatively newer class of insecticide. Used primarily in agriculture, neonicotinoids are also used for flea control in domestic animals. Information on human exposures to neonicotinoids is limited. Neonicotinoid exposures reported to Texas poison centers during 2000–2012 were identified and the distribution by selected factors examined. Of 1,142 total exposures, most products contained imidacloprid (77%) or dinotefuran (17%). The exposures were seasonal with half reported during M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 10 publications
(67 reference statements)
2
37
0
Order By: Relevance
“…The prevalence of voluntary intoxication was diferent from one study to another: only 2% in the study in Texas and 4.9% in the study in France, as opposed to the studies in China and Sri Lanka, where 81% and 82%, respectively, were classiied as an atempt of suicide [25,26,13].…”
Section: Poisoning -From Specific Toxic Agents To Novel Rapid and Simmentioning
confidence: 59%
See 2 more Smart Citations
“…The prevalence of voluntary intoxication was diferent from one study to another: only 2% in the study in Texas and 4.9% in the study in France, as opposed to the studies in China and Sri Lanka, where 81% and 82%, respectively, were classiied as an atempt of suicide [25,26,13].…”
Section: Poisoning -From Specific Toxic Agents To Novel Rapid and Simmentioning
confidence: 59%
“…The patient recovered without complications with supportive treatment and was discharged 4 days after ingestion [24]. Most cases were reported in USA (Texas), France, China and Sri Lanka [25,26,13]. The epidemiological aspects resulting from these studies are summarized in Table 3.…”
Section: Epidemiology Of Acute Poisoning With Neonicotinoids In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors although stated (an often shortcoming also observed in other studies) that no data regarding serum IMI level were available. Forrester (2014) provided an overall picture of NNDs exposure that occurred in Texas, USA, from 2000 to 2012. Of 1,142 exposures the 77% contained IMI and in less extent DINOT (17%).…”
Section: Case Reportsmentioning
confidence: 99%
“…From a clinical perspective, there were 1142 neonicotinoid exposures reported to poison centers in Texas, USA from 2000 to 2012 [13]; most were associated with products containing imidacloprid (77%) or dinotefuran (17%). Exposure to ACE was associated with only 0.5% of the reported incidents.…”
Section: Introductionmentioning
confidence: 99%